Niche Reconstructive Techniques for Complex Abdominal Wall Reconstruction: A Review. Issue 4 (April 2014) - Sue, Gloria R.; Narayan, Deepak
Abdominal wall defects resulting from recurrent hernias, trauma, and radiation necrosis are difficult and challenging to repair given the high rates of recurrence and surgical morbidity. Complex abdominal wall defects often require the transposition of autologous material to bridge the fascial gap. We present a review of niche reconstructive techniques that have been used in complex abdominal wall repair. The specific techniques reviewed include use of delayed and tunneled pedicled tensor fascia lata myofascial flap, de-epithelialized flap closure, free latissimus dorsi myocutaneous flap with or without innervation, and abdominal wall transplant. These niche surgical techniques have great potential to reduce recurrence rates when used in the proper setting for complex abdominal wall reconstruction. More studies are needed to evaluate the relative use of these techniques with the more widely established surgical methods of reconstruction.